Application of Non-drug Methods in the Complex Rehabilitation of Children with Congenital Epidermolysis Bullosa - Olga M. Konova; Tatiana V. Sviridova; Svetlana B. Lazurenko; Irina P. Brazhnikova; Svetlana V. Isaenkova; Nikolay N. Murashkin (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
Congenital epidermolysis bullosa is known to be on the list of rare diseases for which there is no specific treatment. Determining thecontent and means of the rehabilitation program for patients with epidermolysis bullosa is not an easy task and involves a carefulselection of methods for each patient. Aim. The article analyzes the results of the use of non-drug methods in the complex rehabilitation of 90 children (from 6,5 to 18 years)with congenital epidermolysis bullosa. Material and methods. To assess the effectiveness of rehabilitation in the study before and after treatment we used methods ofclinical examination with skin state evaluation and standard psychological and pedagogical examination to determine the degree ofsocial adaptation of patients (analysis of medical and psychological and pedagogical documentation, structured conversation aboutsocial conditions of the child's life, "Color diagnostic test of nervous and mental states and relations" (V.I. Timofeev and Y.I. Filimonenko),the method "Drawing of an unknown animal" (M.Z. Dukarevich, adaptation by A.L. Venger), "The T.V. Dembo-S.Y. Rubinstein Self-AssessmentResearch Method, the Self-Concept Scale" (E. Pierce, L. Harris, adapted by A. M. Prikhozhan), questionnaire "Assessment ofparental compliance" (D.E. Morisky, L.V. Green), questionnaire "Feeling, activity, mood" (V.A. Doskin, N.A. Lavrentieva, V.B. Sharay andM.P. Miroshnikov). The way in which diagnostics was organized varied taking into account the individual psychophysical capabilitiesof the child. Results. The effectiveness evaluation of the complex rehabilitation of children with epidermolysis bullosa showed an improvementin the clinical condition of the children (significant reduction/elimination of dryness and itching of the skin) and the indicators of wellbeing(mean value: before 30 points after 45, p ≤0.05), activity (mean value: before 25 after 34, p ≤0.05), mood (mean value: before 44,after 51, p ≤0.05) of patients (WAM questionnaire), an increase in the degree of parental commitment to treating children (Moriski-Green questionnaire) from medium to medium and high values. Conclusion. The inclusion of physical therapy and psychological and pedagogical methods of assistance in the process of rehabilitationtreatment increases its effectiveness, activates the compensatory potential of the child's body, promotes harmonization of intrafamilyrelationships, and thus improves the quality of life of the child and his or her relatives.